Churg-Strauss Síndrome. A presentation of two cases - Julio López Argüelles; Joan Omar Rojas Fuentes; Ada Sanchez Lozano (Medisur)
Churg-Strauss syndrome is a strange vasculitis that has an annual incidence between 0.5 and 6.8 per million inhabitants (in patients with asthma it ranges between 20 and 60/1000 000 per year) and a prevalence between 7 and 13 per million inhabitants. Its etiology remains unknown, although infectious causes have not been formally ruled out. The clinical course of the syndrome generally goes through three phases: allergic, eosinophilic and vasculitic. Two cases of patients studied and treated in the Neurology Department of the General University Hospital "Dr. Gustavo Lima Aldereguía" in Cienfuegos are presented. They showed how much presentation, course and severity can vary in this disease.